Nutritional condition of school age children. Clinic, anthropo-medical and alimentary assessment - Alina Esther González Hermida; Jesús Vila Díaz; Carmen Emilia Guerra Cabrera; Odalys Quintero Rodríguez; Mariela Dorta Figueredo; José Danilo Pacheco (Medisur)
Background: the study of children´s growth in an appropriate indicator of children health condition and should be used as one of the basis in the practice of preventive medicine. Objective: to determine the nutritional al condition of children of third and sixth grade of elementary schools of Health Area V of Cienfuegos Municipality. Methods: descriptive, observational, cross-sectional and relational study of 445 school age children from 4 elementary schools. A clinic assessment was carried out along with an anthropo-medical evaluation. A qualitative survey was developed to assess the frequency of consumption of different alimentary groups. Results: the relation weight/height in the two genders presents a prevalence of normal weight; undernourishment is more common among females, overweight is more usual among boys and obesity can be found in both genders. The variable weight/age showed one bad-nutrition (for defect) among females, there was a prevalence of bad-nutrition for excess in both genders. There were no children with height under the third percentile, with prevalence of boys and girls tall and very tall. Bronchial asthma was the most common disease. Conclusions: Food consumption in general, taking into account frequency and kind of food, is not the appropriate. There is a relation between positive clinical findings and the anthropometric assessment of weight/height.